Australian fisherman's fish guide : angler's aid to identification, location, habits, and eating qualities of Australian sea fishes - Coleman, Neville, 1938- (Bay Books, 1978)
Over a period of ten years, Neville Coleman has spent some 3 000 hours observing and photographing the marine life which inhabits our waters. The Fisherman's Fish Guide is designed to provide the angler -whether he's a professional or just a keen amateur - with a quick and easy guide to the fish most commonly caught in Australian waters. The book includes colour photographs of fish, photographed in their natural habitat, for easy identification; information on where they live, what they eat, their behaviour and size, range and whether they are edible or to be avoided at all cost. This invaluable little guide should be part of every fisherman's fishing kit. -- Back Cover.